Legal developments on the doctrine of informed consent in Malaysia: challenges for the future - Jahn Kassim, Puteri Nemie (2015)
The Doctrine of Informed Consent has been a significant principle in protecting a patient’s right of self-determination and acknowledging individual autonomy. Its development in Malaysia has been very much influenced by “medical paternalism” which can be seen from the jurisprudential analysis of legal cases since the 1960s. It is not until the decision of the Federal Court of Malaysia in Foo Fio Na v Dr Soo Fook Mun & Anor (2007), in which paternalistic approaches to the doctrine has been abandoned in favour of a more patient centred approach. Since then, the Malaysian judicial cases have developed with emphasis on respecting patient choice and self-determination, rendering patient autonomy into a dominant principle. Nevertheless, the growth of the doctrine has yet to find a balance between theoretical underpinnings and practical applications. A patient centred approach to the doctrine may promote ideals worth pursuing but a successful implementation of these ideals has yet to be realised in practice. Informed consent is not just a principle but a collaborative process by which a patient learns about and understands the purpose, benefits, and potential risks of a medical or surgical intervention, and then agrees to receive the treatment. However, internal and external constraints might operate to prevent full disclosure of benefits and risks which inhibits the complete development of the ideals which the doctrine promotes. These challenges need to be overcome in order to reach the optimal consent process that will ultimately demonstrate the respect for patient autonomy in modern medical settings.